2009
DOI: 10.1097/opx.0b013e31819fa6e2
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Discrimination with Macular Changes Associated with Early AMD

Abstract: Purpose Age-related macular degeneration (AMD) is a condition that progressively reduces central vision in elderly individuals, resulting in a reduced capacity to perform many daily activities and a diminished quality of life. Recent studies identified clinical treatments that can slow or reverse the progression of exudative (wet) AMD and ongoing research is evaluating earlier interventions. Because early diagnosis is critical for an optimal outcome, the goal of this study is to assess psychophysical orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This extrafoveal vision has lower spatial resolution compared to foveal vision. Many studies on low-level visual processing have illustrated the immediate consequences of the loss of foveal vision, e.g., reduced visual acuity and contrast sensitivity (Qiu and Leat, 2009) and deficits in orientation discrimination (Bedell et al, 2009) and shape discrimination (Wang et al, 2002). For a review on psychophysical function in AMD, see Neelam et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…This extrafoveal vision has lower spatial resolution compared to foveal vision. Many studies on low-level visual processing have illustrated the immediate consequences of the loss of foveal vision, e.g., reduced visual acuity and contrast sensitivity (Qiu and Leat, 2009) and deficits in orientation discrimination (Bedell et al, 2009) and shape discrimination (Wang et al, 2002). For a review on psychophysical function in AMD, see Neelam et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Other methods may achieve the same effect. In a recent paper, Bedell et al found that early AMD patients with normal visual acuity had more difficulty in judging the orientation uniformity of a patch of line segments than normal subjects 58. The key feature of this sensitive test was the selection of length of the line segments.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of those methods are firmly established or clinically routine. Recently, Bedell et al developed a functional test based on the orientation discrimination threshold (ODT) that proved effective in identifying patients in the early stage of AMD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%